Optimization of the Bank’s Balance Sheet : Under current and upcoming regulation - Ahlqvist, Jesse (My University, 2023)
Banking business is based on usage of banks’ balance sheet since the core business of the banks is to collect deposits from surplus sector and then loan these deposits for deficit sector. But in the real-world banks just cannot loan out all the deposits they gather since banking is highly regulated industry which means banks have to meet certain regulatory standards. Within the last thirty years the regulation of banking has increased significantly. Starting with the announcement of Basel I accord in 1988. Basel I introduced the minimum capital requirements for banks and also the risk-weighted asset calculations. Basel I was fairly simple framework, and it had its weaknesses which lead to new regulatory framework Basel II. Basel II was more complicated compared to Basel I. It introduced for example the three pillars framework, revised the calculation of risk weighted assets and allowed banks to use internal models to calculate credit risk. Last financial crisis however showed that Basle II was not enough to keep crisis from happening. As an answer Basel III was introduced in 2010. Basel III contained event tighter capital requirements, introduced new liquidity ratios, and set leverage limit for banks. Basel III is the current regulation framework banks have but Basel Committee has introduced some revisions on it which are called Basel IV. Even though this is unofficial term the revisions include some major changes on risk weight calculations. Taking even more risk sensitivity approach. All this means that banks must deal with constantly evolving and more complicated regulation framework and still try maximize their profits. This calls for substantial assets-liabilities management and efforts to achieve the most efficient balance sheet allocations as possible. In this thesis the aim is to briefly introduce the development of the Basel framework and provide some suggestion what the optimal balance sheet structure could look like and make some comparison between Basel III and Basel IV balance sheets to see how the new revisions could affect to banks returns or balance sheet structure. In this thesis banks risk profile has also been taken into account. Which means that the optimization is done with three different sets of constrains. Risk averse banks aims for much higher capital and liquidity ratios than regulation demands while risk seeking banks only wants to meet the regulatory minimum. Neutral risk banks is between of these two. Adding this different risk profiles allows more comprehensive analysis between Basel III and Basel IV balance sheet. The results shows that there are some clear differences between the balance sheets on individual assets/liabilities level but in the broad picture the changes are noticeable but not that drastic. The results indicates that the optimal allocations yield better return on equity with Basel IV regulation on risk averse and neutral risk profiles while Basel III regulation gives better RoE on risk seeking profile.
Keywords: Basel säännöstö, Taseen optimonti